SEKSUAL DALAM AL-QUR’AN - Abdur Rohman (UIN Sunan Kalijaga Yogyakarta, 2019)
Sexual has the meaning of the case relating to intercourse between men and women. Talking about sex is a taboo subject, but the Quran as a holy book talks about it. For this reason, this research will focus on discussing sexual issues discussed in the Quran. This research method uses qualitative technical-library research with a thematic interpretation approach (mawdu‘i). The results of this study conclude that: First, Halal sex can be mapped into six redaction: Rafath means sex because it is identical with dirty things; Mubasharah means sex because of meeting the skin; Qaraba means sex because it is so close; Taghaththa> means coming to have sex; Nikah means sex permisible with Sha>ri’; Dukhul means sex because it includes the male genitalia in the female genitalia for husband and wife. Secondly forbidden sex, al-Qur’an uses the bigha redaction, it is meaning coercion to women to become Prostitute; al-musafihat prostitute women in the context of accusations; Muttakhidat akhdan means mistress; Fahishah means immorality (sex); Zina means unlawful sexual (free sex). Keyword: Sex, Tafsir, Thematics